2023
DOI: 10.1039/d3fo01701j
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus gasseriCKCC1913 mediated modulation of the gut–liver axis alleviated insulin resistance and liver damage induced by type 2 diabetes

Shuaiming Jiang,
Aijie Liu,
Wenyao Ma
et al.

Abstract: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by dysregulation of lipid metabolism, insulin resistance, and gut microbiota disorder. Compared to drug interventions, probiotic interventions may have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…However, the significant negative correlation (P < 0.05) between s_Parabacteroides_merdae and body fat and systemic pressure makes it reasonable to speculate that the enrichment of s_Parabacteroides_merdae can increase the production of short chain fatty acids, thereby reducing the risk of diabetes and the damage to the cardiovascular system. Although blueberry co-exercise did not yield significant results in increasing the abundance of these bacteria in the participants, its strong correlation with systolic blood pressure in hypertensive individuals is a promising sign for moderate improvements in the body, such as the regulation of immune cells and a decrease in inflammation 31,32 .…”
Section: Discussionmentioning
confidence: 87%
“…However, the significant negative correlation (P < 0.05) between s_Parabacteroides_merdae and body fat and systemic pressure makes it reasonable to speculate that the enrichment of s_Parabacteroides_merdae can increase the production of short chain fatty acids, thereby reducing the risk of diabetes and the damage to the cardiovascular system. Although blueberry co-exercise did not yield significant results in increasing the abundance of these bacteria in the participants, its strong correlation with systolic blood pressure in hypertensive individuals is a promising sign for moderate improvements in the body, such as the regulation of immune cells and a decrease in inflammation 31,32 .…”
Section: Discussionmentioning
confidence: 87%
“…As our data indicated, gut microbiota α-diversity was higher in LGG sows when compared to CON sows, consistent with research showing that LGG enhanced α-diversity in an insulin resistance mouse model [ 41 ]. Previous reports also showed that individuals with insulin resistance had lower Lactobacillus abundance [ 42 , 43 ], which could be increased by LGG [ 44 ]. Consistent with these observations, we identified higher Lactobacillus abundance in LGG sows.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of Lactobacillus gasseri strain CKCC1913 in diabetic mice reduced insulin resistance, fasting blood glucose levels, serum levels of pro-inflammatory cytokines (eg, TNF-α and IL-6), and hepatic oxidative stress-induced damage by increasing SOD activity and decreasing malondialdehyde levels. This therapy increased the abundance of beneficial bacteria such as Parabacteroides merdae and the production of short-chain fatty acids (SCFAs) to reduce liver oxidative stress and inflammation [ 28 ] . In vitro treatment of Lactobacillus sakei MJM60958 inhibited oleic acid and cholesterol-induced hepatocyte lipid accumulation.…”
Section: The Role Of Gut Microbiota In Liver Inflammationmentioning
confidence: 99%